Managing type 1 diabetes in the context of work life: A matter of containment. (December 2018) - Hansen, Ulla Møller; Cleal, Bryan; Willaing, Ingrid; Tjørnhøj-Thomsen, Tine
Abstract: For people with type 1 diabetes, extensive tasks involved in diabetes self-management have a significant impact on overall care and quality of life. Members of the working population with type 1 diabetes spend one third of their time at work, yet little attention has been paid to challenges specific to balancing diabetes management and work life. Diabetes is associated with increased absenteeism and presenteeism, as well as disability retirement and lower lifetime income. These quantitative outcomes are corroborated by qualitative studies highlighting some of the challenges of reconciling diabetes self-management with work life. This qualitative study expands on previous research by examining illness behavior in work life using Alonzo's concept of containment. Forty in-depth interviews with Danish people with type 1 diabetes were conducted from May to December 2016 and analyzed using abductive reasoning. We found that working people with type 1 diabetes live in tension between competing logics linked to diabetes and to work life. We illustrate how diabetes management can be articulated as a matter of containment, which refers to the assemblage of practices and mental and emotional work required to keep diabetes at the level of a side-involvement and maintain proper situational involvement in work life. The containment framework illuminates and characterizes diabetes management in the context of work life and reveals a hidden burden of disease carried by working people with type 1 diabetes. Further research is needed to advance the theory of containment. Highlights: A hidden burden of disease exists among people with type 1 diabetes at work. Containment of disease at work requires practices and mental and emotional work. Tension exists between the logic of work and the logic of the patient. Temporality is an omnipresent point of reference for containment.